The influence of abnormal audit fees, independence, and competence on audit quality - Iqbal Deandre Ramadhan; Mochamad Kohar Mudzakar (International Journal of Financial, Accounting, and Management, 2022)
Purpose: The purpose of this study is to determine whether abnormal audit fees, independence, and competence affect the audit quality according to 9 Public Accounting Firms in Bandung. The factors tested in this study are abnormal audit fee, independence, and competence as the independent variables while auditing quality is the dependent variable. Research Methodology: The sampling method used in this study is nonprobability sampling. The reason for choosing the method is the consideration that the selected data sample meets the criteria being tested. The sample selection criteria in this study are auditors in 9 Bandung Public Accounting Firms. In this study, the analysis method was partially (t-test) with a significance of 5%. The data was analyzed by using Version 20 of the Social Science Statistics Package (SPSS). Results: The research results partially and simultaneously indicate that abnormal audit fees, independence, and competence affect audit quality according to the respondent from 9 Public Accounting Firms in Bandung at 52,1%. Limitations: This study only focuses on the effect of abnormal audit fees, independence, and competence on audit quality in only 9 Public Accounting Firms in Bandung. Contribution: The results of the study provide education about audit quality that companies use for the services of auditors and inform future researchers.